Assessment of Malaria Intermittent Preventive Treatment (Ipt) Uptake among Pregnant Women attending Antenatal Care at Kasanje Health Center III, Wakiso District - Kabatongole, Doreen; Ochan, Moses (Student’s Journal of Health Research Africa, 2021)
Background: Malaria in pregnancy is a major public health problem with substantial risks for both the mother and unborn child. Malaria is responsible for 10,000 maternal deaths globally, 20% of stillbirths, and 11% of newborn deaths in sub-Saharan Africa. The study intends to explore the extent of intermittent preventive treatment IPTp uptake among pregnant women attending ANC. Methodology A Cross-sectional survey was carried out among pregnant women attending antenatal care at Kasanje Health Center III to explore the extent of intermittent preventive treatment (IPTp) uptake among pregnant women attending ANC. Data on their socio-demographic characteristics and antenatal service utilization were collected using a questionnaire and review of antenatal care (ANC) cards. In-depth interviews were conducted and data on ANC service delivery collected and analyzed. Univariate, Bivariate and multiple logistic regression analyses were done to determine factors associated with uptake of IPTp. Results: A total of 75 pregnant women were interviewed, all in reproductive age 15-48 years, with an average age of 25.6years. All the respondents (100%) had attended antenatal care at least once. 58% of the participants wherein their third trimester. Many, 31% were on their second visit, 24% on their 3rd visit while only 10% were on their first visit. The majority of the participants (88%) had their ANC started in the first trimester. It was also noted that the number of IPTp varied significantly with the number of ANC visits (chi2=33.8, p<0.001). The majority (62.67) of the participants knew IPTp and the majority of the respondents (99%) knew how malaria is transmitted. Abortion was mentioned as the major outcome of malaria in pregnancy (95%) followed by Stillbirths (72%). Conclusion and recommendations: An increased number of ANC visits, providing IPTp information to pregnant women, and the gestational age of pregnancy resulted in increased uptake of IPTp.